First record of the Bermuda grass scaleOdonaspis ruthae Kotinsky, 1915 (Hemiptera: Coccomorpha: Diaspididae) in Colombia - Montes Rodríguez, José Mauricio; Kondo, Takumasa (University of Nebraska–Lincoln, 2025)
The Bermuda grass scale Odonaspis ruthae Kotinsky, 1915 (Hemiptera: Coccomorpha: Diaspididae) is reported for the first time in Colombia. The scale insect was collected in two localities, in northwestern and southwestern Colombia. This is the first record of the tribe Odonaspidini in Colombia. Aspects of the distribution and biology of the species are discussed. A key to separate the species of Odonaspis recorded in the Neotropical region is provided.